Καταγραφή, Κωδικοποίηση και Ψηφιοποίηση τυπογραφικών εκφάνσεων στο Ιστορικό Κέντρο της Πόλης της Λεμεσού - Καραγιάννης, Χαράλαμπος (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2018)
This thesis examines the typography that exists in the historic city center of Limassol. Also, the aim of this thesis is to record, code the typographic signs which are placed in the historical center of the city and then digitization. In the first part of the research a bibliographic review was made regarding the history of Limassol. Also investigating the advertising in Cyprus and the evolution that accrued. Subsequently, using the above information, the signs were collected, analyzed with coders and then categorized. The result of the research was digitization of the typographic signs as a website that is the digital museum of Limassol typography.
Keywords: digital museum, Limassol, typography, linguistic landscape, typographic signs; τυπογραφικές εκφάνσεις, ψηφιακό μουσείο, γλωσσικό τοπίο, Λεμεσός